Practical Approach to Children Presenting with Eosinophila and Hypereosinophilia - Costagliola, Giorgio; Marco, Serena D.; Comberiati, Pasquale; D'Elios, Sofia; Petashvili, Nino; Di Cicco, Maria Elisa; Peroni, Diego (Current Pediatric Reviews, 2020)
Eosinophilia is not a rare finding in clinical practice, and often poses problems in terms of etiologic research and differential diagnosis. Peripheral eosinophilia is defined by a blood eosinophil count > 500 cells/μL. It is classified into mild (500-1500 cells/μl), moderate (1500-5000 cells/μl) and severe for an eosinophil count > 5000 cells /μl. The term
Keywords: DRESS